ОСНОВНІ НАПРЯМИ РОЗВИТКУ ЕЛЕКТРОННОГО ВРЯДУВАННЯ В КРАЇНАХ-ЧЛЕНАХ ЄС У СФЕРІ СОЦІАЛЬНОГО ДІАЛОГУ: ЦИФРОВІ ПЛАТФОРМИ, КОЛЕКТИВНІ ПЕРЕГОВОРИ, АВТОМАТИЗАЦІЯ ПРОЦЕСІВ, КОНСУЛЬТАЦІЇ З ГРОМАДСЬКІСТЮ - Klykov, Anatolii (Zhytomyr Ivan Franko State University, 2025)
The article offers a thorough and comprehensive analysis of the key trends in the development of e-government in the European Union member states within the broader context of the transformation of social dialogue. The author provides an in-depth examination of the political, institutional, and technological foundations of digitalisation in social partnership, with particular emphasis on the relevance of EU regulatory frameworks – including the eIDAS Regulation, the Open Data Directive, the Web Accessibility Directive, and the strategic initiatives underpinning the Digital Europe Programme. The study convincingly demonstrates that digital instruments function not merely as technological innovations but as catalysts for the modernization of social dialogue, enhancing transparency, inclusiveness, and stakeholder participation. A notable strength of the article lies in its use of practical examples from Finland, Estonia, Greece, and Portugal, which illustrate the diversity of national approaches to integrating digital tools into social dialogue mechanisms. By analyzing the functioning of e-consultation platforms, integrated service portals, electronic identification systems, and data infrastructures, the author shows how these solutions improve the quality and evidence-based nature of policy formulation. Special attention is paid to the emerging use of automation and semantic text analysis, which are reshaping the administrative and analytical dimensions of collective bargaining and consultation processes. The article is characterized by a clear structure, academic rigor, and effective use of up-to-date EU policy documents and institutional sources. The topic is highly relevant given the ongoing digital transformation of public administrations and the growing need for efficient, inclusive, and data-driven decision-making. The work will be valuable for scholars and practitioners in the fields of labor relations, public policy, digital governance, and European studies, and it may also serve as a useful resource for teaching and applied research.